Genome wide association study of SNP-, gene-, and pathway-based approaches to identify genes influencing susceptibility to Staphylococcus aureus infections - Ye, Zhan; Vasco, Daniel A.; Carter, Tonia C.; Brilliant, Murray H.; Schrodi, Steven J.; Shukla, Sanjay K. (Frontiers in Genetics, 2014)
Background: We conducted a genome-wide association study (GWAS) to identify specific genetic variants that underlie susceptibility to disease caused by Staphylococcus aureus in humans. Methods: Cases (n=309) and controls (n=2,925) were genotyped at 508,921 single nucleotide polymorphisms (SNPs). Cases had at least one laboratory and clinician confirmed disease caused by S. aureus whereas controls did not. R-package (for SNP association), EIGENSOFT (to estimate and adjust for population stratification) and gene- (VEGAS) and pathway-based (DAVID, PANTHER, and Ingenuity Pathway Analysis) analyses were performed. Results: No SNP reached genome-wide significance. Four SNPs exceeded the p< 10-5 threshold including two (rs2455012 and rs7152530) reaching a p-value < 10-7. The nearby genes were PDE4B (rs2455012), TXNRD2 (rs3804047), VRK1 and BCL11B (rs7152530), and PNPLA5 (rs470093). The top two findings from the gene-based analysis were NMRK2 (pgene=1.20E-05), which codes an integrin binding molecule (focal adhesion), and DAPK3 (pgene=5.10E-05), a serine/threonine kinase (apoptosis and cytokinesis). The pathway analyses identified epithelial cell responses to mechanical and non-mechanical stress. Conclusion: We identified potential susceptibility genes for S. aureus diseases in this preliminary study but confirmation by other studies is needed. The observed associations could be relevant given the complexity of S. aureus as a pathogen and its ability to exploit multiple biological pathways to cause infections in humans.